Detection of caprine paratuberculosis (Johne's disease) in pre- and post-vaccinated herds: morphological diagnosis, lesion grading, and bacterial identification - Stefanova, Elena Plamenova; Sierra, Eva; Fernández, Antonio; Quesada-Canales, Oscar; Paz-Sánchez, Yania; Colom-Rivero, Ana; Espinosa de los Monteros, Antonio; Herráez, Pedro; Domínguez, Lucas; Bezos, Javier; Pérez-Sancho, Marta; Moreno, Inmaculada; et al. (Frontiers in Veterinary Science, 2024)
Samples from the mesenteric lymph nodes (MS LNs) and ileocecal valves (ICV) of 105 goats, comprising 61 non-vaccinated and 44 vaccinated against Mycobacterium avium subspecies paratuberculosis (MAP), were collected at slaughter from a farm with a confirmed history of paratuberculosis (PTB). These goats had subclinical infections. PTB-compatible lesions in the MS LNs, ICV lamina propria (LP), and Peyer's patches (PPs) were graded separately. Furthermore, the load of acid-fast bacilli was quantified using Ziehl-Neelsen staining (ZN), MAP antigens by immunohistochemistry (IHC), and MAP DNA by PCR targeting the IS900 sequence. Gross PTB-compatible lesions were found in 39% of the goats, with 31.72% vaccinated (V) and 68.29% non-vaccinated (nV). Histopathological lesions induced MAP were observed in 58% of the animals, with 36.07% vaccinated and 63.93% non-vaccinated. The inclusion of histopathology as a diagnostic tool led to a 28% increase in diagnosed cases in MS LNs and 86.05% in ICV. Grade IV granulomas with central mineralization and necrosis were the most common lesions in MS LNs. In the ICV, mild granulomatous enteritis with multifocal foci of epithelioid macrophages was predominant, occurring more frequently in the PPs than in the LP. Furthermore, statistical differences in the presence of histopathological lesions between vaccinated and non-vaccinated goats were noted in MS LNs, ICV LPs, and ICV PPs. Non-vaccinated animals showed higher positivity rates in ZN, IHC, and PCR tests, underscoring the benefits of anti-MAP vaccination in reducing PTB lesions and bacterial load in target organs. Our findings emphasize the necessity of integrating gross and histopathological assessments with various laboratory techniques for accurate morphological and etiological diagnosis of PTB in both vaccinated and non-vaccinated goats with subclinical disease. However, further studies are required to refine sampling protocols for subclinical PTB in goats to enhance the consistency of diagnostic tools.